6‐Nitro‐Quinazolin−4(3H)−one Exhibits Photodynamic Effects and Photodegrades Human Melanoma Cell Lines. A Study on the Photoreactivity of Simple Quinazolin−4(3H)−ones. (21st January 2021) - Panagopoulos, Anastasios; Balalas, Thomas; Mitrakas, Achilleas; Vrazas, Vassilios; Katsani, Katerina R.; Koumbis, Alexandros E.; Koukourakis, Michael I.; Litinas, Konstantinos E.; Fylaktakidou, Konstantina C.
Abstract: Photochemo and photodynamic therapies are minimally invasive approaches for the treatment of cancers and powerful weapons for competing bacterial resistance to antibiotics. Synthetic and naturally occurring quinazolinones are considered privileged anticancer and antibacterial agents, with several of them to have emerged as commercially available drugs. In the present study, applying a single‐step green microwave irradiation mediated protocol we have synthesized eleven quinazolinon−4(3 H )−ones, from cheap readily available anthranilic acids, in very good yields and purity. These products were irradiated in the presence of pBR322 plasmid DNA under UVB, UVA and visible light. Four of the compounds proved to be very effective DNA photocleavers, at low concentrations, being time and concentration dependent as well as pH independent. Participation of reactive oxygen species was related to the substitution of quinazolinone derivatives. 6‐Nitro‐quinazolinone in combination with UVA irradiation was found to be in vitro photodestructive for three cell lines; glioblastoma (U87MG and T98G) and mainly melanoma (A−375). Thus, certain appropriately substituted quinazolinones may serve as new lead photosensitizers for the development of promising biotechnological applications and as novel photochemo and photodynamic therapeutics. Abstract : Quinazolin‐4(3 H )‐ ones upon derivatization may become photo‐sensitizers and release Reactive Oxygen Species (ROS) and/or other radicals able to destroy biological targets. 6‐Bromo and 6‐iodo quinazolin‐4(3 H )‐ ones release ROS as well as radicals derived from the homolysis of C‐halogen bond at 312 nm. 6‐ and 7‐Nitro quinazolin‐4(3 H )‐ones exhibit photodynamic effects with the creation of singlet oxygen and other ROS under UVA (365 nm) and visible light, at low concentrations. 6‐Nitro quinazolin‐4(3 H )‐ one effectively kills A375 aggressive melanoma cells at 50 μm concentration and irradiation at 365 nm. Quinazolin‐4(3 H )‐ one derivatives maybe used as lead compounds for photo‐dynamic therapy and other "on demand" light‐driven biotechnological applications.